Exploring Ionospheric Disturbances Using GNSS: A STEM-Based Investigation of the 2024 Extreme Geomagnetic Storm - Pansong, Chollada; Buakao, Nitipat; Keokhumcheng, Thanapon; Phothila, Pharinya; Intamas, Patcharin; Kenpankho, Prasert (My University, 2025)
This study investigates the effectiveness of a STEM-based instructional approach integrating GNSS satellite technology and ionospheric TEC (Total Electron Content) analysis during extreme geomagnetic storms. The objective was to enhance students' conceptual understanding, practical skills, and STEM-related attitudes through interdisciplinary learning activities. The SPACE model (Study, Plan, Analyze, Create, Evaluate) was applied as a pedagogical framework to guide students through real-world TEC anomaly detection using GPS RINEX data and computational tools. The integration of real satellite data and hands-on analysis enabled students to connect theoretical knowledge with real-world phenomena, deepening their engagement and inquiry-based thinking. Pre-and post-test results revealed statistically significant improvements, with scores increasing from a mean of 5 1. 8 (S D = 7. 5 4) to 7 5. 0(S D= 7.42) (p < 0. 000001). Moreover, the STEM Attitude Questionnaire reflected strong positive perceptions, especially in STEM career motivation (x¯=4.20) and perceived value of STEM (x¯= 4.13). These findings highlight the model's potential to foster STEM readiness. Integrating GNSS-based TEC analysis into the STEM framework significantly enhanced students' academic outcomes, practical skills, and STEM attitudes.
Keywords: Extreme geomagnetic storm; Global Navigation Satellite System (GNSS); STEM; Total electron content